0274 Occupational Noise Exposure and the Prevalence of Hyperglycemia. (23rd June 2014) - Yu, Tzu-Yi; Liu, Chiu-Shong; Young, Li-Hao; Chang, Ta-Yuan
Abstract : Objectives: This cross-sectional study aimed to investigate the association between occupational noise exposure and the prevalence of hyperglycemia among workers. Method: We recruited 532 volunteers in a machinery and equipment manufacturing factory as the study population in Central Taiwan. The walk-through survey was performed to identify the workplaces with noise levels above 80 A-weighted decibel (dBA) first and then the noise dosimeter was used to conduct personal time-weighted-average sound levels. After assigning each subject to a similar exposure group, we classified all subjects into high-exposure (noise levels ≥85 dBA, n = 91), median-exposure (80≤ noise levels <85dBA, n = 62), low-exposure (noise levels <80 dBA, n = 76) and reference groups (officers, n = 303). Logistic regressions were applied to estimate the risk of hyperglycemia by different exposure groups after controlling for potential confounders. Results: The mean noise levels of high-exposure, median-exposure, low-exposure and office workers were 89.5 ± 2.90 dBA, 83.4 ± 0.4 dBA, 76.7 ± 1.1 dBA and 71.4 ± 4.0 dBA, respectively, and there was a significant difference between groups (p < 0.001). The prevalence of hyperglycemia among high-exposure, median-exposure, low-exposure and office workers were 10.2%, 13.2%, 11.3% and 9.9%, respectively. After controlled for age, sex, education level, body mass index, cigarette smoking, alcohol drinking and regular exercise, the odds ratio of hyperglycemia between the high-exposure and office workers was 3.96 (95% confidence interval = 0.83–18.83), which had a marginal difference (p = 0.08). Conclusions: Occupational noise exposure above 85 dBA might be associated with the increasing prevalence of hyperglycemia. Future studies should be conducted to demonstrate the potential causality of occupational noise and hyperglycemia.